Proceedings of the 2018 ACM/IEEE International Conference on Human-Robot Interaction 2018
DOI: 10.1145/3171221.3171260
|View full text |Cite
|
Sign up to set email alerts
|

Robots And Racism

Abstract: Most robots currently being sold or developed are either stylized with white material or have a metallic appearance. In this research we used the shooter bias paradigm and several questionnaires to investigate if people automatically identify robots as being racialized, such that we might say that some robots are "White" while others are "Asian", or "Black". To do so, we conducted an extended replication of the classic social psychological shooter bias paradigm using robot stimuli to explore whether effects kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 41 publications
(60 reference statements)
3
35
0
Order By: Relevance
“…These findings are consistent with prior research indicating the automaticity at which social biases extend to and affect behavior in HRI (e.g., [17], [21], [22], [46], [30]). Moreover, the findings support indications by a growing body of literature (containing instances of unprovoked abuse towards robots -e.g., [47], [48]; as well as less empathy for robots relative to that for people when witnessing or participating in their abuse -e.g., [49], [50]) that people more readily engage in the dehumanization of robots.…”
Section: B Links To Existing Literature and Broader Implicationssupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with prior research indicating the automaticity at which social biases extend to and affect behavior in HRI (e.g., [17], [21], [22], [46], [30]). Moreover, the findings support indications by a growing body of literature (containing instances of unprovoked abuse towards robots -e.g., [47], [48]; as well as less empathy for robots relative to that for people when witnessing or participating in their abuse -e.g., [49], [50]) that people more readily engage in the dehumanization of robots.…”
Section: B Links To Existing Literature and Broader Implicationssupporting
confidence: 92%
“…Here we examined the associations between racialization, ontology, and the manifestation of antisocial responding towards emergent robot platforms. Motivated by prior research, which highlights the automaticity at which bias and stereotyping extend to HRI (e.g., [27], [30], we evaluated the degree to which people responded negatively and dehumanizingly towards robots of varying racialization (Asian, Black, and White) versus other people of similar social cues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding race, Bartneck et al () showed that participants automatically ascribed a race to robots according their color (e.g., white, black) and extended human racial stereotypes to racialized robots. Moreover, using the shooter bias paradigm, Addison, Yogeeswaran, and Bartneck () showed that racial stereotypes interfere with time decision: participants were slower to decide to not to shoot unarmed White robots than unarmed black robots.…”
Section: Drawbacks To the Humanization Of Robotsmentioning
confidence: 99%
“…Given the breadth of effects that robots are expected to have on human life, the infusion of harmful forms of bias into the design and functioning of robotic technology must be scrutinized and hopefully halted. For example, a recent article in the ACM/IEEE International Conference on Human-Robot Interaction entitled "Robots and Racism" examined how research subjects react to a robot if they assume the robot has been "racialized"; the scenario was conducted under the guise of a shooter bias task [1]. The researchers illustrated that subjects' reaction time when deciding to shoot a robot differs depending on the "skin tone" of the robot.…”
Section: :2mentioning
confidence: 99%